Strengthening Students' Tolerance in Using Digital Conversation Applications at Smpn 9 Mataram - Nurcholis Ariyan Pratama; Almira Wulandari; Ayu Wahdania; Baiq Ispiyunita; Yunita Utami Putri (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to identify students' tolerance attitudes in using digital conversation applications at SMPN 9 Mataram. This research uses a phenomenological type of qualitative research method by collecting data through interviews, observation and documentation. The research subjects were teachers and students at SMPN 9 Mataram. The results of the research show that, (1) Students' tolerance attitudes in using conversation applications are good in terms of respecting friends of different religions, being able to restrain emotions and being open to accepting diversity among students, (2) Factors that influence students' attitudes of tolerance are seen from an environmental perspective. family, school, community, and various content on digital media, (3) Effective ways to strengthen students' attitudes of tolerance, namely implementing P5 with the theme "global diversity and embracing diversity", joint Imtaq activities, as well as supervision and guidance by the homeroom teacher.